Police Misconduct: Mapping its Location, Seriousness and Theoretical Underpinning. (24th October 2017) - Moss, Brian
Abstract: Police misconduct and the location of street crimes and deviance have received much research attention. The location of police misconduct, by contrast, has not. Taking the case of Ireland, where policing underwent significant reform in 2007, police oversight data are mapped to determine the location and nature of complaints and any clustering of police misconduct, particularly in areas of greatest deprivation usually associated with people coming into most frequent contact with police. The implications of the findings for police, police oversight, and existing theories by which geography of deviance is framed are discussed.